The philosophy of Gandhi : a study of his basic ideas - Richards, Glyn (Curzon Press, 1991)
Seeks to give a coherent account of Gandhi's basic ideas. The book begins with an analysis of his central concept of "truth", and proceeds to show how a "prima facie" abstract concept so determines his way of life that it becomes the raison d'etre of his existence.
Keywords: Gandhi, -- Mahatma, -- 1869-1948.; Gandhi, -- Mahatma, -- 1869-1948; PHILOSOPHY -- Hindu.